PENGADOPSIAN ASAS PROPORSIONALITAS DALAM KONTRAK KERJA BERDASARKAN UNDANG UNDANG CIPTA KERJA - Muhammad Firman Ahsan (JOURNAL SAINS STUDENT RESEARCH, 2025)
An employment agreement serves as the legal foundation for the relationship between workers and employers, providing a reference for the protection of rights and the implementation of obligations between the parties. In an agreement, it is essential to ensure that the parties are positioned on an equal footing in order to establish a proportional contract. This study discusses the urgency of applying the principle of proportionality in employment contracts under the Job Creation Law, as well as the legal protection afforded to the parties bound by such contracts under the same law. This research is a normative legal study employing a statutory approach and supported by data obtained through literature study. The results of this study indicate that the application of the principle of proportionality in employment contracts is crucial to achieving balance, justice, and legal certainty between workers and employers from the formation stage to the termination of the employment relationship. This principle plays a significant role in ensuring that the distribution of rights and obligations is carried out fairly according to the respective roles of each party. In addition, the Job Creation Law provides legal protection for workers in the form of guarantees of fair wages, social security, and protection from unilateral termination of employment, as well as for employers in the form of legal certainty, flexibility in managing employment relations, and effective mechanisms for resolving labor disputes. Thus, the application of the principle of proportionality becomes an essential instrument in creating a fair, balanced, and mutually protective employment relationship between workers and employers.